Toward better assessments of developmental toxicity using stem cell‐based in vitro embryogenesis models. Issue 16 (31st January 2022) - Marikawa, Yusuke
Abstract: In the past few decades, pluripotent stem cells have been explored as nonanimal alternatives to assess the developmental toxicity of chemicals. To date, numerous versions of stem cell‐based assays have been reported that are allegedly effective. Nonetheless, none of the assays has become the gold standard in developmental toxicity assessment. Why? This article discusses several issues in the hope of facilitating the refinement of stem cell assays and their acceptance as the cornerstone in predictive developmental toxicology. Each stem cell assay is built on a limited representation of embryogenesis, so that multiple assays are needed to detect the diverse effects of various chemicals. To validate and compare the strengths and weaknesses of individual assays, standardized lists of reference chemicals should be established. Reference lists should consist of exposures defined by toxicokinetic data, namely maternal plasma concentrations that cause embryonic death or malformations, and also by the effects on the molecular machineries that control embryogenesis. Although not entirely replacing human or animal tests, carefully selected stem cell assays should serve as practical and ethical alternatives to proactively identify chemical exposures that disturb embryogenesis. To achieve this goal, unprecedented levels of coordination and conviction are required among research and regulatory communities.